Prospective evaluation of a closed-incision negative pressure wound therapy system in kidney transplantation and its association with wound complications - Lam, Susanna; Huynh, Annie; Ying, Tracey; Sandroussi, Charbel; Gracey, David; Pleass, Henry C.; Chadban, Steve; Laurence, Jerome M. (Frontiers in Nephrology, 2024)
Introduction Wound complications can cause considerable morbidity in kidney transplantation. Closed-incision negative pressure wound therapy (ciNPWT) systems have been efficacious in reducing wound complications across surgical specialties. The aims of this study were to evaluate the use of ciNPWT, Prevena™, in kidney transplant recipients and to determine any association with wound complications. Material and methods A single-center, prospective observational cohort study was performed in 2018. A total of 30 consecutive kidney transplant recipients deemed at high risk for wound complications received ciNPWT, and the results were compared to those of a historical cohort of subjects who received conventional dressings. Analysis for recipients with obesity and propensity score matching were performed. Results In total, 127 subjects were included in the analysis. Of these, 30 received a ciNPWT dressing and were compared with 97 subjects from a non-study historical control group who had conventional dressing. The overall wound complication rate was 21.3% (27/127). There was no reduction in the rate of wound complications with ciNPWT when compared with conventional dressing [23.3% (7/30) and 20.6% (20/97), respectively, p = 0.75]. In the obese subset (BMI ≥30 kg/m2), there was no significant reduction in wound complications [31.1% (5/16) and 36.8% (7/19), respectively, p = 0.73]. Propensity score matching yielded 26 matched pairs with equivalent rates of wound complications (23.1%, 6/26). Conclusion This is the first reported cohort study evaluating the use of ciNPWT in kidney transplantation. While ciNPWT is safe and well tolerated, it is not associated with a statistically significant reduction in wound complications when compared to conventional dressing. The findings from this study will be used to inform future studies associated with ciNPWT in kidney transplantation.